Immune Responses in Post Kala-azar Dermal Leishmaniasis - Chatterjee, Mitali (Indian J Dermatol, 2020)
Kala-azar, commonly known as visceral leishmaniasis (VL), is a neglected tropical disease that has been targeted in South Asia for elimination by 2020. Presently, the Kala-azar Elimination Programme is aimed at identifying new low-endemic foci by active case detection, consolidating vector control measures, and decreasing potential reservoirs, of which Post Kala-azar Dermal Leishmaniasis (PKDL) is considered as the most important. PKDL is a skin condition that occurs after apparently successful treatment of VL and is characterized by hypopigmented patches (macular) or a mixture of papules, nodules, and/or macules (polymorphic). To achieve this goal of elimination, it is important to delineate the pathophysiology so that informed decisions can be made regarding the most appropriate and cost-effective approach. We reviewed the literature with regard to PKDL in Asia and Africa and interpreted the findings in establishing a potential correlation between the immune responses and pathophysiology. The overall histopathology indicated the presence of a dense, inflammatory cellular infiltrate, characterized by increased expression of alternatively activated CD68+ macrophages, CD8+ T cells showing features of exhaustion, CD20+ B cells, along with decreased CD1a+ dendritic cells. Accordingly, this review is an update on the overall immunopathology of PKDL, so as to provide a better understanding of host-parasite interactions and the immune responses generated which could translate into availability of markers that can be harnessed for assessment of disease progression and improvement of existing treatment modalities.